Risk profile, clinical presentation, and determinants of stroke subtypes among patients with stroke admitted to public referral hospitals, Northwest Ethiopia in 2021: A cross-sectional study - Ayehu, Gashaw Walle; Yitbarek, Getachew Yideg; Zewdie, Edgiet Abebe; Amsalu, Bedemariam Tadesse; Abie, Yonatan; Atlaw, Daniel; Agegnehu, Assefa; Admasu, Fitalew Tadele; Azanaw, Melkalem Mamuye; Amare, Abraham Tsedalu; Emiru, Zemen Asmare (Frontiers in Neurology, 2022)
Background Stroke is the second leading cause of death worldwide, with a significant increase in stroke burden over the last two and half decades, especially in developing countries. African countries are undergoing an epidemiological transition from being dominated by infectious diseases to being double-burdened by non-communicable diseases, with existing infectious diseases driven by sociodemographic and lifestyle changes and a weak healthcare system. Data on the risk profile, clinical presentation, and predictors of stroke subtypes are still limited. Therefore, the main aim of this study was to assess the risk profile, clinical presentation, and predictors of stroke in public referral hospitals of Northwest Ethiopia. Methods For this study, 554 patients with stroke admitted to three public referral hospitals were prospectively followed up. Data were collected using a pre-tested interviewer-administered questionnaire. STATA version 16 was used for data analyses. Candidate variables significant in bivariate analysis were selected for multivariate binary logistic regression, and statistical significance was set at a p < 0.05. Results Of the 554 patients with stroke, 60.3% had an ischemic stroke. The mean age of the participants was 61 ± 12.85 years, and more than half (53.25%) of them were women. The most common risk factor identified was hypertension (29.7%), followed by congestive heart failure. The most common clinical presentation was hemiparesis, which was reported by 57.7% of the patients, followed by loss of consciousness (20.7%) and aphasia (9%). Through multivariable logistic regression, age (AOR = 1.03, 95% CI:1.01–1.05), sedentary physical activity level (AOR = 6.78, 95% CI:1.97–23.32), absence of a family history of chronic illness (AOR = 3.79, 95% CI:2.21–6.48), hypertension (AOR=0.51, 95% CI:0.31–0.85), and past stroke (AOR = 3.54, 95% CI:0.93–13.49) were found to be independent determinants of the stroke subtype. Conclusion Age, the level of sedentary physical activity, absence of a family history of chronic illness, hypertension, and past stroke were independent determinants of stroke subtype.